Prediction of network pharmacology and molecular docking-based strategy to determine potential pharmacological mechanism of Liuwei Dihuang pill against tinnitus. Issue 46 (18th November 2022) - Wu, Zhongbiao; Zhu, Zhongyan; Cao, Jian; Wu, Weikun; Hu, Shiping; Deng, Chengcheng; Xie, Qiang; Huang, Xinmei; You, Chengkun
Abstract : Background: Liuwei Dihuang Pill is widely used to treat tinnitus in China. However, the underlying mechanism of Liuwei Dihuang Pill in treating tinnitus still remains unclear. Objective: To explore the potential pharmacological mechanism of Liuwei Dihuang Pill in the treatment of tinnitus based on network pharmacology and molecular docking. Methods: The active components of the Liuwei Dihuang Pill were obtained from the traditional Chinese medicine systems pharmacology database and analysis platform (TCMSP) database. Cytoscape software was used to draw the active component-target network diagram of Liuwei Dihuang Pill, and obtain the core components. Then the corresponding targets were also obtained from the TCMSP database. Targets related to tinnitus were obtained from the GeneCards, DisGeNET, TTD and DrugBank databases. The String database was used to construct protein–protein interaction (PPI) network of common targets of drugs and diseases, then the core targets were screened out. The Annotation, Visualization and Integrated Discovery (DAVID) database was used for gene ontology (GO) enrichment and Kyoto encyclopedia of genes and genomes (KEGG) pathway analysis of common targets. Finally, the molecular docking between the core component and the core target was carried out by AutoDock. Results: The core components of Liuwei Dihuang Pill in the treatment of tinnitus including quercetin, stigmasterol, kaempferol, β-sitosterol, tetrahydroalstonine, which may act on core targets such as STAT3, transcription factor AP-1 (JUN), tumor necrosis factor (TNF), interleukin-6 and MAPK3. HIF-1 signaling pathway, Influenza A, P53 signaling pathway, and Toll-like receptor signaling pathway play a role in anti-inflammatory, improving microcirculation in the blood-labyrinth barrier, increasing cochlear blood flow, and preventing hair cell damage. The molecular docking results showed that the affinity between core components and core targets was good. Conclusion: The potential mechanism of Liuwei Dihuang Pill in the treatment of tinnitus was preliminarily discussed in this study, which may provide a theoretical basis and evidence for further experimental research.